Pelatihan Penyusunan Proses Bisnis Akuntansi dan Keuangan di Kabupaten Pasuruan - Abdul Ghofar; Muhammad Jusuf Wibisana; Dian Surya Ayu Fatmawati; Areta Widyakusuma; Varin Wilda Rahmadia (Jurnal Pengabdian Kampus, 2023)
The purpose of this community service is to provide training to the Pasuruan Regency BPKPD in the preparation of business processes. This needs to be done because the Pasuruan Regency Financial and Revenue Management Agency needs to prepare a business process map in accordance with the Regulation of the Minister for Administrative Reform and Bureaucratic Reform No. 19 of 2018 concerning Business Process Maps. The hope is that it can become a reference for Pasuruan Regency BPKPD in describing effective and efficient working relationships between organizational units to produce performance according to Pasuruan Regency's vision and mission in order to increase added value for stakeholders of the Financial and Regional Revenue Management Agency in Pasuruan Regency.